ANALYSIS OF THE ISLAMIC COMMERCIAL BANK PERFORMANCE IN INDONESIA DURING THE COVID-19 PANDEMIC - Frizky, Mochamad Yulian; Adabi, Muhammad Akmal Chesta; Naufanda, Abiyyu Raafi; Nurafini, Fira; Canggih, Clarashinta (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
This paper aims to analyze the differences in the Financial Performance of Islamic Commercial Banks in Indonesia during the COVID-19 Pandemic by comparing several financial ratios, i.e., Return on Assets (ROA), Return on Equity (ROE), Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR) and Capital Adequacy Ratio (CAR). The data used are quarterly financial data from 2020 to 2022 published by 11 Islamic Commercial Banks on the official website of the Financial Services Authority (OJK). The research was conducted using quantitative methods with a comparative approach. The study results show differences in the financial performance of the 11 Islamic Commercial Banks during the COVID-19 pandemic. The most significant differences can be seen in the ratios of ROA, ROE and NPF, where the development of these three ratios fluctuated from 2020 to 2022. As for the ratios of FDR and CAR, there were also significant differences between the 11 banks. Even so, all the Islamic Commercial Banks studied had good financial performance during the COVID-19 pandemic. The results of this study are expected to contribute to policy or regulatory makers to improve the financial performance of Islamic commercial banks in Indonesia.